GC-MS Analysis of Main Chemical Constituents and Antioxidative Potential of Propolis from Meghalaya, India - Ibanrikynti Turnia; Rajesh Prasad; Surya Bali Prasad (Journal of Global Pharma Technology, 2020)
Objective: Propolis or bee glue is a complex resinous honey bee product known to possess several useful pharmacological properties.Propolis is becoming increasingly popular because of its potential role in contributing to human health. The chemical composition and biological characteristics of propolis depend upon plant sources accessible to bees, bee species, geographical region and seasons. Method: In the present study, the main chemical constituents of propolis sample from Meghalaya were analyzed using gas chromatography-mass spectrometry (GC-MS) technique. The antioxidant properties of the same propoliswere also determined by chemical assays such as 2,2-diphenyl-1-picrylhydrazyl (DPPH), superoxide anion, hydroxyl radical scavenging activity, and metal chelating activity. Results: GC-MS analysis identified twenty different groups of compounds, out of which eight compounds along with their biological activity were recorded. The main constituents of propolis from Meghalaya were N-hexadecanoic acid (34.88%), oleic acid (26.37%), tetradecanoic acid (4.90 %), 2-furancarboxaldehyde,5-(hydroxymethyl) (3.21%) and 3,7,11,15-tetramethyl-2-hexadecene-1-ol (1.95%). The propolisshowed significant antioxidant activity in all the assays. The antioxidant activity of the propolis may also include other chemical constituents not detected through GC-MS analysis. Conclusion: The findings demonstrate thatpropolis from Meghalaya is a rich source of natural antioxidants and should be very useful in the preventionof various free radicals related diseases.Keywords: Propolis, GC-MS, antioxidant activity